MBCL-10. TREATMENT OUTCOMES AND COMPLICATION RATES OF SINGLE VERSUS TANDEM AUTOLOGOUS TRANSPLANT FOR REGIMENS FOR MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Plant, Ashley S; Ma, Clement; Shyr, Derek; Lee, Michelle A; Chi, Susan N
Abstract: Treatment outcomes for medulloblastoma have improved with the use of craniospinal irradiation and chemotherapy but such therapy has resulted in poor neurologic outcomes for young patients. For children < 6 years old, chemotherapy-only regimens with autologous transplant have been implemented with the intention of avoiding long-term neurologic sequelae. It is not yet known whether single or tandem autologous transplantation is superior with respect to efficacy and/or safety. We performed a retrospective review of children with medulloblastoma treated at Dana-Farber Cancer Institute/Boston Children's Hospital from 1996 to 2016 with either single or tandem autologous transplantation after completion of induction chemotherapy. We compared overall survival (OS), event free survival (EFS), clinical factors, and complication rates between patients who received single vs tandem transplants. Among 24 patients, 12 (50%) received tandem transplants. Median age at diagnosis was 3.0 years (interquartile range [IQR] = 2.3-4.3) and median follow up time was 3.6 years (IQR = 2.0-7.9). There was no significant difference in extent of resection (p = 0.32) but a trend towards more metastatic disease (p=0.09) in the single transplant group. There was no difference in 5-year OS (69.51% (+/-12.41)) and EFS (p>0.66) between groups. Trends towards longer antibiotic duration (p = 0.20) and increased number of platelet transfusions (p = 0.10) were seen with the tandem regimen though shorter hospital stay per transplant (p =0.01) and faster time to engraftment (p=0.0005). Despite the single transplant group having double the number of patients with metastatic disease, survival and safety outcomes were similar between the two transplant approaches.